Coronary Artery Ectasia- a review - Hossen, Md Jakir (International Journal of Medical and Dental Research, 2022)
Coronary artery ectasia (CAE) is an extreme type of expansive vascular remodelling (i.e. excessive expansive remodelling) as a result of atherosclerotic plaque formation; atherosclerosis being the most prevalent cause. Despite being identified more than 50 years ago, the clinical relevance of CAE is not well-defined, and its therapy is still a matter of discussion. In this review paper, we have highlighted the aetiology, pathophysiology, and currently recommanded treatment of coronary artery ectasia based on all accessible literature from PubMed and other international journals.